Concordance of Drug-resistance Profiles Between Persons With Drug-resistant Tuberculosis and Their Household Contacts: A Systematic Review and Meta-analysis. (25th May 2020) - Chiang, Silvia S; Brooks, Meredith B; Jenkins, Helen E; Rubenstein, Dana; Seddon, James A; van de Water, Brittney J; Lindeborg, Michael M; Becerra, Mercedes C; Yuen, Courtney M
Abstract: Background: Household contacts of patients with drug-resistant tuberculosis (TB) are at high risk for being infected with Mycobacterium tuberculosis and for developing TB disease. To guide regimen composition for the empirical treatment of TB infection and disease in these household contacts, we estimated drug-resistance profile concordance between index patients with drug-resistant TB and their household contacts. Methods: We performed a systematic review and meta-analysis of studies published through 24 July 2018 that reported resistance profiles of drug-resistant TB index cases and secondary cases within their households. Using a random-effects meta-analysis, we estimated resistance profile concordance, defined as the percentage of secondary cases whose M. tuberculosis strains were resistant to the same drugs as strains from their index cases. We also estimated isoniazid/rifampin concordance, defined as whether index and secondary cases had identical susceptibilities for isoniazid and rifampin only. Results: We identified 33 eligible studies that evaluated resistance profile concordance between 484 secondary cases and their household index cases. Pooled resistance profile concordance was 54.3% (95% confidence interval [CI], 40.7–67.6%; I 2 = 85%). Pooled isoniazid/rifampin concordance was 82.6% (95% CI, 72.3–90.9%; I 2 = 73%). Concordance estimates were similar in a subanalysis of 16 studies from high-TB-burden countries. There were insufficient data to perform a subanalysis among pediatric secondary cases. Conclusions: Household contacts of patients with drug-resistant TB should receive treatment for TB infection and disease that assumes that they, too, are infected with a drug-resistant M. tuberculosis strain. Whenever possible, drug susceptibility testing should be performed for secondary cases to optimize regimen composition. Abstract : In a meta-analysis of 33 studies, we found 82.6% (95% confidence interval [CI]: 72.3–90.9%) concordance in isoniazid and rifampin susceptibilities among tuberculosis cases in the same household. When additional drugs were considered, concordance was 54.3% (95% CI, 40.7–67.6).